1984
DOI: 10.1038/clpt.1984.24
|View full text |Cite
|
Sign up to set email alerts
|

Cimetidine interaction with imipramine and nortriptyline

Abstract: The interaction between cimetidine and two tricyclic antidepressants was examined in healthy subjects. One tricyclic, imipramine, is primarily metabolized to a demethylated active metabolite, desipramine. The other, nortriptyline, is largely metabolized to a 10-hydroxylated metabolite. It was assumed that pretreatment with cimetidine, because of its inhibition of metabolic pathways of both demethylation and hydroxylation as well as its ability to reduce hepatic extraction of these drugs, would increase bioavai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1985
1985
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The authors concluded that cimetidine inhibited the N-demethylation of imipramine and the hydroxylation of desipramine. Henauer and Hollister (1984) reported a similar decrease in imipramine total clearance following a single dose after 4 days' pretreatment with cimetidine in 6 subjects. In addition, they found a 37% decrease in the volume of distribution of imipramine.…”
Section: Antidepressants and Antipsychoticsmentioning
confidence: 55%
“…The authors concluded that cimetidine inhibited the N-demethylation of imipramine and the hydroxylation of desipramine. Henauer and Hollister (1984) reported a similar decrease in imipramine total clearance following a single dose after 4 days' pretreatment with cimetidine in 6 subjects. In addition, they found a 37% decrease in the volume of distribution of imipramine.…”
Section: Antidepressants and Antipsychoticsmentioning
confidence: 55%
“…Those studies that have found a relationship between concentration and response have found an inverse U-shaped relationship between parent drug concentration and clinical response of obsessive-compulsive disorder, while the depression associated with obsessive compulsive disorder showed an inverse U-shaped relationship between metabolite concentrations and clinical response)58] Where a relationship was found, the best plasma concentration ranges for therapeutic effect were 100 to 250 Ilg/L for clomipramine and 230 to 550 Ilg/L for norclomipramine) 59,60] The most important drug interaction with clomipramine is the possible induction of serotonin syndrome when clomipramine is administered within 14 days of administration of a monoamine oxidase inhibitor (MAOI). Plasma concentrations of this drug are reportedly increased by haloperidol, [61] methylphenidate,f361 cimetidine [35) and fluoxetine. [34) Clomipramine increases serum concentrations of phenobarbital (phenobarbitone), and blocks the pharmacodynamic effect of some antihypertensives.…”
Section: Clomipraminementioning
confidence: 99%
“…Abernethy et al (1983b) reported that the administration of cimetidine 300mg 4 times daily with imipramine 50mg in 6 volunteers resulted in increases in the absolute bioavailability and AVC of imipramine; the increase in half-life was not statistically significant. A similar investigation was carried out by Henauer and Hollister (1984) in 6 healthy volunteers; cimetidine pretreatment increased the bioavailability of imipramine and decreased its clearance. The decreased clearance is considered to be a result of an inhibitory effect of cimetidine on hepatic metabolism (Sallee & Pollock 1990).…”
Section: Antidepressantsmentioning
confidence: 75%
“…have reported that cimetidine increased nortriptyline concentrations in 1 patient but did not mention any clinical sequelae from the increased concentrations. A study in 6 volunteers showed no changes in the pharmacokinetics of nortriptyline with cimetidine pretreatDrug Safety 7 (4) 1992 ment; however, the bioavailability of the 10-hydroxy metabolite of nortriptyline was increased (Henauer & Hollister 1984). As the pharmacological activity of the metabolite is unknown, the clinical significance of this finding is unclear.…”
Section: Antidepressantsmentioning
confidence: 93%